Contact sensitivity responses in mice infected with Trypanosoma cruzi. - Reed, S G (1978)
Mechanisms of depression of contact sensitivity responses in C57BL/10 mice infected with Trypanosoma cruzi were studied. Cellular involvement during sensitization with oxazolone was investigated in mice acutely infected with T. cruzi. Contact sensitivity was not expressed in mice during the latter stages of the acute infection. Spleen cells from sensitized, infected mice which were unable to respond to oxazolone could confer contact sensitivity upon normal syngenic mice as effectively as spleen cells from uninfected, sensitized donors. The ability of mice infected with T. cruzi to respond to an eliciting dose of oxazolone was significantly improved when macrophages from normal syngenic donors were administered to them at the time of skin test. When either normal or infected mice were used as recipients of lymphocytes from sensitized donors, the normal mice responded significantly better than did infected mice after administration of an eliciting dose of oxazolone. An increase in pyroninophilic cells was observed in draining lymph nodes after application of a sensitizing dose of oxaxolone to the ears of either normal or acutely infected mice. These results indicate that suppression of contact sensitivity during acute T. cruzi infection is directed toward the efferent arm rather than the afferent arm of the response.